Optimization of Polysulfone/Polyethylene Glycol (PSf/PEG) Casted Solution Composition as a Membrane Electrolyte in a Dye-Sensitized Solar Cell (DSSC) - Cahyani, Sinta Anjas; Kusumawati, Nita (Jurnal Pijar Mipa, 2024)
Stability is the main challenge in developing electrical energy made from sunlight, namely Dye-Sensitized Solar Cell (DSSC). The DSSC system comprises a photoanode, electrolyte, comparison electrode, and dye sensitizer with a photoelectrochemical working principle. Dye sensitizer and electrolyte are the main components that determine the stability of DSSC, with problems such as solvent evaporation leakage in liquid electrolytes and dye desorption. In overcoming these problems, the polymer electrolyte of Polysulfone/Polyethylene Glycol (PSf/PEG) is a solution to the problem by increasing the mobility of I-/I3- ions in the electrolyte. Polymer composition and porogen (pore formers) affect the ionic conductivity, which impacts the electron flow of the DSSC system. Therefore, this study optimized the composition of PSf/PEG polymer electrolyte, namely 18/0, 17/1, 16/2, 15/3, 14/4, and 13/5. This research was carried out using quantitative methods with data processed in a quantitative descriptive manner to determine the performance of DSSC based on PSf/PEG membrane electrolyte. The wavelength absorption of the dye was characterized using a Spectrophotometer UV-Vis instrument, and the specific wavelength was obtained at 573 nm, which indicates anthocyanin absorption. Electrochemical characterization of the dye using voltammetry yielded a resulting energy bandgap value of 0.5132 eV with the touch plot method. Testing the performance and stability of DSSC, voltage, and current measurements were carried out using a multimeter, and fill factor and efficiency calculations were carried out. The performance of DSSC with liquid electrolytes was 1.66%, while that of DSSC with membrane electrolytes of the best composition (16/2) was 1.38% at 0 hours. In addition, the performance test was carried out at 72 hours of exposure time, resulting in an efficiency of 0.77%, while the DSSC with the best composition of membrane electrolyte (16/2) was 1.11%. This shows a decrease in the efficiency of DSSC with liquid electrolytes by 53.43%, while the membrane electrolyte efficiency of DSSC is 19.33-20.17%.